Trust and technology transfers - García-Vega, María; Huergo, Elena (Elsevier, 2017)
Research and development is largely done by multinationals (MNEs) that transfer technology to their foreign subsidiaries. Trust might be an important determinant of the governance of technology transfers because trust can reduce the dependence of the subsidiary on the headquarters. We empirically investigate how widely held perceptions of the trustworthiness of the host economy influence international technology transfers that subsidiaries receive from their business group or from other international providers. We use firm-level data on R&D imports from foreign subsidiaries operating in Spain for the period 2005 to 2012, and a Eurobarometer measure of trust between citizens of European countries. We find that subsidiaries that belong to MNEs from countries with higher trust in Spaniards have fewer technology transfers within the business group and more from international market channels than subsidiaries from countries with lower trust in Spaniards. Our results support predictions of transaction cost economics about how technology transfers are organized.